Feasibility study of hybrid renewable energy system design for a typical high-rise building in Malaysia - Khan M.R.B.; Pasupuleti J. (Alpha Publishers, 2023)
This article presents the Hybrid Renewable Energy System project plan (HRES) representation for high rise building in Malaysia. A building has been for this study since it signifies a distinctive load profile for many highrise buildings in Malaysia. A techno-economic investigation has been performed to establish the possibility of PV, and battery system installation to reduce network dependence. The methodology started with information collection of load summary and solar resources at the selected location. Then, HOMER software was used by the analysis of hybrid financial and technological analysis configurations. Sensitivity examination was conducted to analyze system presentation under load and grid price changes. Results of analyses includes net present cost (NPC), energy cost (COE) and environmental pollution (CO2). This feasibility findings shows that the gridonly communication has the most promising results with the lowest NPC, preceded by the PV and battery grid system. 2020 Alpha Publishers.